STUDI KOMPARATIF PENYELESAIAN SENGKETA EKONOMI MELALUI PENGADILAN NIAGA DAN ARBITRASE - Murniati, Rilda (Lampung University)
Formally, the economics of alternative dispute resolution can be done through the Commercial Court and Arbitration. Both are different in terms of the object of dispute, the procedures for dispute resolution and legal consequences. In terms of the object of dispute the equation is the Commercial Court and Arbitration courts can be resolving disputes in the field of property rights along a predetermined interlektual in UUHKI. While the difference is the scope of Arbitration has a broad field that encompasses all economic fields of trade, finance, industry, banking, and everything related to the rights of the parties. Commercial Court only has the authority in the field of IPR and bankruptcy as well as the postponement of debt payment obligations.Â Keywords: Economic Dispute Resolution, Commercial Court of Arbitration